2014
DOI: 10.1007/s12032-014-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

CISD2 expression is a novel marker correlating with pelvic lymph node metastasis and prognosis in patients with early-stage cervical cancer

Abstract: The CDGSH iron sulfur domain2 (CISD2) is an evolutionarily conserved gene. It functions to control mammalian life span and regulate human breast cancer cells proliferation. However, the characteristics of CISD2 expression and its clinical/prognostic significance are unclear in human tumor. Our study aimed to investigate the expression pattern and clinicopathological significance of CISD2 in patients with early-stage cervical cancer. The mRNA and protein expression levels of CISD2 were analyzed in eight cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Enhanced expression of the 2Fe-2S protein NAF-1 is associated with the onset and progression of multiple cancer types (10,11,(14)(15)(16)(17)(18)(19). To determine whether elevated NAF-1 levels play a direct role in tumor development, we stably overexpressed NAF-1 in MDA-MB-231 cells [NAF-1(+)] and generated xenograft tumors in nude mice.…”
Section: Naf-1 Overexpression Results In a Dramatic Augmentation In Xmentioning
confidence: 99%
See 3 more Smart Citations
“…Enhanced expression of the 2Fe-2S protein NAF-1 is associated with the onset and progression of multiple cancer types (10,11,(14)(15)(16)(17)(18)(19). To determine whether elevated NAF-1 levels play a direct role in tumor development, we stably overexpressed NAF-1 in MDA-MB-231 cells [NAF-1(+)] and generated xenograft tumors in nude mice.…”
Section: Naf-1 Overexpression Results In a Dramatic Augmentation In Xmentioning
confidence: 99%
“…Taken together, our findings suggest that any drastic change in the lability of the NAF-1 cluster would impair its function in maintaining the levels of iron and ROS in mitochondria under control. Altering NAF-1 cluster lability via different drugs could therefore be used to treat different cancers that depend on NAF-1 overexpression for their proliferation (10,11,(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is involved in longevity [16], and in mice several studies indicated that suppressed expression of cisd2 led to shortened life spans [88]. In human pathologies mNT and NAF-1 were shown to be involved in diabetes and obesity [89, 90], neurodegeneration and cardiovascular abnormalities, and skeletal muscle maintenance [13, 29, 91], they were also implicated in autophagy, apoptosis [18, 21, 23, 92], aging [16, 93] and cancer [22, 23, 90, 9497]. In addition, NEET proteins are implicated in the rare genetic disease Wolfram Syndrome 2 (WFS-2).…”
Section: Neet Protein Involvement In Diseasesmentioning
confidence: 99%